The Difference Between Night and Morning Exercise in the Running Community to Physiologycal Recovery - Areta, Handyan; Arfiansyah, Rengga Dio; Maharan, Eidelweis Yusida; Atha, Naufal Fathin; Pratiwi, Bunga Mayang Eka (Journal of English Language and Education, 2025)
This study aimed to examine the difference between morning and evening training sessions on physiological recovery among members of a running community in Surabaya. A quantitative approach with a descriptive retrospective design was applied. Twenty participants were divided into two groups: morning runners and evening runners. Data were collected through an online questionnaire including the Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality, the Profile of Mood States (POMS) to evaluate mood state, and Resting Heart Rate (RHR) measurement as an indicator of physiological recovery. Data were analyzed using the independent samples t-test to compare both groups. The results revealed no significant difference between morning and evening runners in terms of sleep quality (p=0.978), mood state (p=0.784), and resting heart rate (p=0.819). These findings suggest that training time does not directly influence physiological recovery as long as the exercise is performed consistently and supported by a healthy lifestyle. Therefore, body adaptation to exercise is more affected by sleep habits, stress levels, and consistent training routines rather than the timing of the activity.